Wabah Penyakit Menular dalam Sejarah Islam dan Relevansinya dengan Covid-19 - Muhammad Rasyid Ridho (JUSPI (Jurnal Sejarah Peradaban Islam), 2020)
In writing this article, an understanding of the epidemic, year, and Covid-19 will be presented. Global understanding and the difference between plague and year. In this article, we will discuss how the plague occurred in the past, namely during the Caliphate of Umar bin Khattab, in particular. The purpose of this article is to seek wisdom and relevance in the history of the past, nature in facing outbreaks which can later be used as a solution in dealing with the outbreak, especially in dealing with Covid-19 and generally for dealing with future outbreaks. The characteristics of this study are to present the flow of the outbreak and its handling during Umar bin Khattab's time, then present the handling of the Covid-19 pandemic at this time. The research method used is ethnographic method and case study, namely action research of a group and cases that occur.